Desenvolvimento e validação de metodologias SPE/HPLC para a determinação de estrógenos e fitoestrógenos em águas superficiais - Edilene, Dantas Teles Moreira (2015)
In this work were developed and validated two analytical methodologies using solid phase extraction and High Performance Liquid Chromatography (HPLC), for identification and quantification of endocrine disruptors in surface water. A methodology was used to analyze four estrogens: 17 β-estradiol, ethinyl estradiol, estrone and estriol, and the other methodology was used to analyze six phytoestrogens: biochanin A, genistin, genistein, daidzin, daidzein and formononetin. In the sample preparation step we developed an extraction method using solid phase extraction (SPE).The used cartridges were effective in the extraction for both estrogens and phytoestrogens using 1000 ml of river sample, and reached a pre-concentration factor of 2,857 times and recoveries above 90%. The proposed method uses fluorescence detector for estrogens, while the one for the phytoestrogens uses diode array detector. On methods validation were evaluated analytical performances for both methods. The selectivity shows that there was no presence of interfering peaks in both evaluated methods. The generated calibration curves presented good linearity and good correlation coefficients (above 0.99) for all studied analytes. The curves linearity was evaluated by an ANOVA and analysis of graphical residue which showed that the model shows no lack of fit. The limit of detection (LOD) and of quantification (LOQ) for estrogens and phytoestrogens determined in this study were similar to the observed values in other studies and therefore were considered appropriate for the evaluated matrix type. The accuracy of the methods was assessed by the repeatability and intermediate precision, which presented CV <13%. The accuracy was assessed using the recovery test, which was in the range of 72.9 -113%). In the evaluated stability, standard solutions of both methods were stable for a period of 30 days under refrigeration. The results showed that the proposed methods are reliable and have been validated successfully. After validated the methods were applied in the analysis of water samples from the Cuiá River, located in João Pessoa, Paraíba (Brazil), on different collection points, and three sampling campaigns. In all campaigns it was observed the presence of the four estrogens and phytoestrogens six in concentrations ranging from 1.40 to 4754 ng L-1 for estrogens and 3.58 to 2210 μg. L-1 to phytoestrogens in the aquatic studied system.